Analisis Risiko Produksi Sorgum (Sorghum bicolor) sebagai Pakan Alternatif di PT Juang Jaya Abdi Alam - Rinaldi, Al-Bara Fuad; Noer, Irmayani; Anggraini, Nuni; Zaini, Muhammad (Universitas Galuh, 2025)
Global warming is increasingly impacting the agricultural sector. Climate change such as prolonged drought affects crop production and productivity. PT Juang Jaya Abdi Alam is a company engaged in cattle fattening, facing challenges in providing quality green fodder. The impact of lack of green fodder on livestock health can result in slow weight gain. The purpose of this study was to analyze the risks in sorghum production used as an alternative feed for livestock at PT Juang Jaya Abdi Alam. This research method uses a descriptive method with data and information obtained processed qualitatively and quantitatively. The analysis method uses descriptive analysis and coefficient of variation (CV) production risk analysis. The results of the study showed that the sources of sorghum production risk include; the influence of weather and climate, pest and disease attacks, selection of agricultural inputs, and technical errors of workers. The results of the production analysis showed a CV value of 0.41 where the resulting CV value is smaller than 0.5, meaning that the risk of sorghum production at PT JJAA is in the low category. The lower limit of production is 2,093.35, which means that the lowest possible production risk of sorghum cultivation per farm per planting season is 2,093.35 kg/farm.